PENGARUH KUALITAS LABA AKUNTANSI TERHADAP EFISIENSI INVESTASI PERUSAHAAN DENGAN RISIKO LITIGASI SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2011-2012) - Risha Aristiani N; Agus Purwanto (Diponegoro Journal of Accounting, 2015)
This study examines the moderating effect of litigation risk on the influence of earning quality on investment efficiency. Litigation risk mitigates agency problems and promote greater earning quality. Higher litigation risk would strengthen the influence of earning quality on investment efficiency. Manager avoid litigation because it raises costs. That’s why income statement will be approached with the actual state of the company so that it can be used as a proper basis for making investment decisions. The result indicates litigation risk had significant negative to the influence of earning quality on Investment efficiency. This negative effect states that the higher litigation risk would reduce accrual quality on investment efficiency. In other words, earning quality will further improve corporate investment efficiency. Litigation risk has a role to influence managers to disclose earning.